Neutrophil to lymphocyte ratio is not related to carotid atherosclerosis progression and cardiovascular events in the primary prevention of cardiovascular disease: Results from the IMPROVE study. (11th November 2021) - Mannarino, Massimo R.; Bianconi, Vanessa; Gigante, Bruna; Strawbridge, Rona J.; Savonen, Kai; Kurl, Sudhir; Giral, Philippe; Smit, Andries; Eriksson, Per; Tremoli, Elena; Veglia, Fabrizio; Baldassarre, Damiano; et al.
Abstract: Inflammation is a component of the pathogenesis of atherosclerosis and is associated with an increased risk of atherosclerotic cardiovascular disease (ASCVD). The neutrophil to lymphocyte ratio (NLR) is a possible inflammation metric for the detection of ASCVD risk, although results of prospective studies are highly inconsistent on this topic. We investigated the cross‐sectional relationship between NLR and carotid intima‐media thickness (cIMT) in subjects at moderate‐to‐high ASCVD risk. The prospective association between NLR, cIMT progression, and incident vascular events (VEs) was also explored. In 3341 subjects from the IMT‐Progression as Predictors of VEs (IMPROVE) study, we analyzed the association between NLR, cIMT, and its 15‐month progression. The association between NLR and incident VEs was also investigated. NLR was positively associated with cross‐sectional measures of cIMT, but not with cIMT progression. The association between NLR and cross‐sectional cIMT measures was abolished when adjusted for confounders. No association was found between NRL and incident VEs. Similarly, there were no significant differences in the hazard ratios (HRs) of VEs across NLR quartiles. NLR was neither associated with the presence and progression of carotid atherosclerosis, nor with the risk of VEs. Our findings do not support the role of NLR as a predictor of the risk of atherosclerosis progression and ASCVD events in subjects at moderate‐to‐high ASCVD risk, in primary prevention. However, the usefulness of NLR for patients at a different level of ASCVD risk cannot be inferred from this study.